Respuesta :
Hello!!!
To solve the system of linear equations, you need to isolate y to one side.
y=-2x+1
3x-y=-6
From here, you use the substitution method:
Substitute the first equation into the second
3x-(-2x+1)=-6
Distribute the -1, and be careful!!!!
3x+2x-1=-6
Combine like terms
5x-1=-6
Add 1 to both sides
5x=-5
Divide by 5
x=-1
And x=-1 is the first part of your answer. To find the second part, or y, you need to plug x back into the first equation.
y=-2x+1
y=-2(-1)+1
y=2+1
y=3
And your complete answer is x=-1 and y=3
Hope this helps!!!
To solve the system of linear equations, you need to isolate y to one side.
y=-2x+1
3x-y=-6
From here, you use the substitution method:
Substitute the first equation into the second
3x-(-2x+1)=-6
Distribute the -1, and be careful!!!!
3x+2x-1=-6
Combine like terms
5x-1=-6
Add 1 to both sides
5x=-5
Divide by 5
x=-1
And x=-1 is the first part of your answer. To find the second part, or y, you need to plug x back into the first equation.
y=-2x+1
y=-2(-1)+1
y=2+1
y=3
And your complete answer is x=-1 and y=3
Hope this helps!!!